2021
DOI: 10.1093/asj/sjab109
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Tissue Stromal Vascular Fraction to Platelet-Rich Plasma Supplemented Lipofilling Does Not Improve Facial Skin Quality: A Prospective Randomized Clinical Trial

Abstract: Background Lipofilling has become popular as a treatment to improve aging related skin characteristics (eg, wrinkles, pigmentation spots, pores, or rosacea). Different additives such as platelet-rich plasma (PRP) or stromal vascular fraction (SVF) have been added to lipofilling to increase the therapeutic effect of adipose derived stromal cells (ASCs). Objectives In this study, we hypothesized that mechanical isolated SVF aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Of which, 359 were excluded: 38 papers were not in English, 41 were review articles, 279 articles were not reporting recipient site complications, 1 was not on human subjects. A total of 103 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of which, 359 were excluded: 38 papers were not in English, 41 were review articles, 279 articles were not reporting recipient site complications, 1 was not on human subjects. A total of 103 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies concerning to combination of PRP application and fat grafts were found, and three of those were RCTs [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Eight articles fell under the category "reconstruction," focusing on chronic ulcers and wounds (three), scars (three), or breast reconstruction (two).…”
Section: Resultsmentioning
confidence: 99%
“…Many factors had to be considered, such as differences in number of PRP applications or the use of activators. In seventeen studies [10, 11, 13-15, 21, 24, 27, 31, 34, 35, 38, 40-42, 50, 53], double spin centrifugation was performed, 21 studies used a single spin protocol [16, 17, 19-23, 29, 30, 32, 33, 36, 37, 43-49, 51, 58], and twelve authors merely disclosed the name of the device used, or no information about this process at all [12, 18, 25, 26, 28, 39, 52, 54-57, 59]. Twenty-two authors reported the use of CaCl and/or Thrb for platelet activation [11, 13-15, 18, 19, 21, 24, 28, 30, 31, 37, 39, 42-47, 50, 51, 58].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations